A comprehensive investigation of the differential interaction of human serum albumin with gold nanoparticles based on the variation in morphology and surface functionalization. Issue 58 (31st May 2016) - Alex, Sruthi Ann; Chakraborty, Debolina; Chandrasekaran, N.; Mukherjee, Amitava
Abstract : A systematic investigation on the effect of gold nanoparticle morphology and surface functionalization on the differential interaction of HSA was performed. Abstract : The increasing utilization of nanoparticles for biological applications necessitates the understanding of the interaction of these nanoparticles with biomolecules. Hence, the current study systematically investigated the effect of gold nanoparticle (AuNP) morphology (nanorods and nanospheres) and surface functionalization (CTAB and PEG) on a protein abundant in the blood serum, namely human serum albumin (HSA) using multiple spectroscopic techniques. The UV-visible and fluorescence spectroscopic results indicated that PEGylated AuNPs showed less ground-state complex formation and less disruption in the Trp domain when compared to CTAB-capped AuNPs, which correlated with the lower mean hydrodynamic size observed using dynamic light scattering analysis and higher activation energy required for complex formation. Further experiments have also been performed to suggest the formation of the AuNP–HSA complex. Using synchronous fluorescence, the change in the hydrophobic environment of the Trp domain was also observed to be higher for CTAB-AuNPs. Conformational stability of CTAB-AuNPs was also found to be lower in comparison to PEG-AuNPs from denaturation studies. These results were correlated with the higher secondary structural damage observed for CTAB-AuNPs compared to PEGylated counterparts using circular dichroism (CD) and FTIR analyses. The zeta potential measurements suggested that the positive charge of CTAB also becomes an additional factor that results in a higher aggregation level. Throughout the study, gold nanostructures that have rod-shaped morphology were found to cause more damage than spherical nanoparticles, but the level of protein denaturation could be considerably reduced by replacing the functionalization of the nanoparticles with PEG.